2019
DOI: 10.1039/c9ta02566a
|View full text |Cite|
|
Sign up to set email alerts
|

Steering the crystallization of perovskites for high-performance solar cells in ambient air

Abstract: We developed a “humidity-insensitive antisolvent method” for highly efficient PSCs by steering the crystallization of perovskite precursor films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…1e, the decorated CsPbBr 3 QDs can only enhance the absorption for a narrow range (400-500 nm) in comparison with CH 3 NH 3 PbI 3 −x Cl x layer solely. Furthermore, we also calculated the bandgap of QDs according to the Tauc equation [39][40][41][42][43][44] as shown in Additional file 1: Figure S1. The bandgap is about 2.38 eV.…”
Section: Resultsmentioning
confidence: 99%
“…1e, the decorated CsPbBr 3 QDs can only enhance the absorption for a narrow range (400-500 nm) in comparison with CH 3 NH 3 PbI 3 −x Cl x layer solely. Furthermore, we also calculated the bandgap of QDs according to the Tauc equation [39][40][41][42][43][44] as shown in Additional file 1: Figure S1. The bandgap is about 2.38 eV.…”
Section: Resultsmentioning
confidence: 99%
“…However, a high humidity environment promotes the growth of nuclei, which results in a larger grain size with poor coverage (Figure 4b). [98] The mild humid environment of 30-50% RH was considered as the optimal condition for perovskite film fabrication. [63,96,97,99,100] For example, the perovskite films annealed at a RH of 30-40% obtained the PCE of 17.1%, but when the humidity was increased to 80%, the PCE was reduced to 12.1%.…”
Section: Ambient Exposure: One-step Spin-coatingmentioning
confidence: 99%
“…The best device of CsPbI 3 based inorganic PSCs achieved a PCE of 15.91% under 50% RH. As discussed in Section 2.2.1, Wang et al [98] reported that the atmospheric humidity can steer the crystallization process of perovskite films through affecting the evaporation of the precursor solvent. It was also found that the conventional antisolvent method, which was aimed at controlling the solvent evaporation, failed when the RH was higher than 70%, as the evaporation of solvent was strongly suppressed under high RH.…”
Section: Substrate Preheatingmentioning
confidence: 99%
“…The bandgap of conventional OIMHP films is at the range of 1.5-1.6 eV, and the corresponding theoretical Shockley-Queisser limit efficiency (TS-QLE) is higher than 30% [2][3][4]. However, the reported highest PCE is much lower than the TS-QLE due to the trap-assisted non-radiative recombination in the perovskite film [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%